Updates in Sleep Neurology and Obstructive Sleep Apnea 2021
DOI: 10.5772/intechopen.82756
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is a frequent sleep disorder characterized by repetitive interruption of ventilation caused by partial or complete collapse of the upper airway during sleep. OSA is highly prevalent in the world and it has been associated with cardiovascular disease and cognitive impairment in children and adults. The cognitive impairment in individuals with OSA includes deficiencies in attention and constructional abilities, delayed long-term visual and verbal memory, and executive functions. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Apnea is defined as a reduction in respiratory amplitude of > 80% for 10 s or longer during overnight polysomnography (Ayalon et al, 2010;Harper et al, 2013;Kumar et al, 2014;Lutsey et al, 2016). Cognitive impairment is fairly common in untreated moderate-to-severe COSA, with particular deficits in attention, specifically vigilance, acquisition of new memories, visuospatial abilities, and executive functions (Otero et al, 2019). These deficits frequently co-occur with mood disorders.…”
Section: Intermittent Hypoxiamentioning
confidence: 99%
“…Apnea is defined as a reduction in respiratory amplitude of > 80% for 10 s or longer during overnight polysomnography (Ayalon et al, 2010;Harper et al, 2013;Kumar et al, 2014;Lutsey et al, 2016). Cognitive impairment is fairly common in untreated moderate-to-severe COSA, with particular deficits in attention, specifically vigilance, acquisition of new memories, visuospatial abilities, and executive functions (Otero et al, 2019). These deficits frequently co-occur with mood disorders.…”
Section: Intermittent Hypoxiamentioning
confidence: 99%
“…Previous studies showed that children with OSA display several issues in physical health [ 12 ], development [ 14 ], and comprehensive cognitive functions [ 15 17 , 19 , 22 24 ]. Shpirer et al [ 38 ] showed that hypoxemia correlated with attentional dysfunction in children with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The complications of OSA in children include physiological and physical complications including impaired cardiac function (pulmonary arterial hypertension, heart dilation, chronic cardiac dysfunction, and increased in right heart afterload) [ 12 , 13 ], impaired growth and development [ 14 ], and failure to thrive [ 15 ]. In addition to physical complications, OSA has detrimental effects on behavior and cognition [ 16 , 17 ], development [ 14 ], emotional state [ 18 , 19 ], quality of life [ 18 , 20 , 21 ], attention ability [ 19 , 22 ], and cognitive function [ 19 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“… 30 , 31 Several pathological changes accompany OSA and increase the risk of cognitive dysfunctions such as intermittent hypoxia, disturbed sleep, systemic inflammation, increased oxidative stress, comorbidities, and daytime sleepiness. 32 …”
Section: Discussionmentioning
confidence: 99%